Leadership and the effectiveness of talent management in multinational enterprise : a case study - Chew, Poh Leng (2018)
This research provides empirical evidence on the links between Leadership and Effectiveness of Talent Management. Talent Management is one of the prevalent concern in the large organization. The challenges to global talent management can be derived into exogenous and endogenous. The exogenous drivers could be globalization, demographics, and gap in demand-supply; while the endogenous drivers could be organizational structure and required competencies. MNEs will continue to face the formidable challenge, and if left unmet, will impact of global business strategy, both in the short and long term. With the aim of improving leadership competencies, analogous in improving the chances to continue success in MNEs setting. Importantly, in the context of this research, there have been relatively few insights about Leadership influencing the outcome of Talent management in South East Asia region, especially when considering the acceleration of emerging market contribution to global economic development. Primary data collection from 154 employees of a chosen organization from FMCG sector with a quantitative research of questionnaire and enriched with a series of semi-structured interview with eight human resource and business managers. Descriptive and inferential analysis with regression model is used to test the hypothesis on the importance of Leadership towards objectives measures of the effectiveness of Talent management. The results are both statistically significant. This research found that Leadership is important towards the Effectiveness of Talent Management. Although all three Leadership dimension (Leading Organization, Leading Others and Leading Oneself) are important and discovered that Leading Oneself is strongly correlated to the Effectiveness of Talent management. These core findings present the evidence recommends that organization to develop Shared Value Ecosystem by embracing the People with Purpose value with guiding principles. MNEs shall consider initiating Social Relationship Succession Planning to sustain business continuity and leveraging on the diversity in South East Asia region via people forum and technology-savvy intrapreneurship. The recommendation to MNEs to introduce career counselor role in supporting individuals to bring out the best of them. The research discovered that individuals are key implication with regards to Leadership dimension and correlated to Effectiveness of Talent Management, and an integrative framework is presented as a conclusion.